2018
DOI: 10.21093/di.v18i1.880
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Foreign Language Anxiety and Oral Performance of Non-English Major University Students in Indonesia

Abstract: This study was conducted to investigate the relationship between Foreign Language Anxiety (FLA) and spoken performances of non-English major university students in Indonesia. The study found that learners experienced various degrees of FLA with the mean score 93.07 (SD = 17.69, N = 119). This study also found a statistically significant, negative correlation between the learners' FLA and their achievements as measured by their grades, r (117) = -.37, p < .01. Consistent with that, significant, negative relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 40 publications
5
40
1
Order By: Relevance
“…The structural equation modeling run to answer the first question of the study indicated that all components of speaking were lower than 0.30, showing significance and they all, were in a negative and significant correlation with anxiety, the sample size was adequate for running the model and the structural regression model enjoyed a good fit to show that the components of speaking had significant contributions to their latent variable and all components of speaking performance were in a negative correlation with anxiety. These results are consistent with those of other researchers (Mazouzi, 2013;Thornbury, 2005;Woodrow, 2006;Brown, 2000;Mahripah, 2014;Tanveer, 2007;Kayaoğlu & Sağlamel, 2013;Hanifa, 2018;Baran-Łucarz, 2013;Mahmoodzadeh, 2012;Suleimenova, 2013;Dewaele & Ip, 2013;Leong & Ahmadi, 2017;Subekti, 2018;Zheng & Cheng, 2018;Liu, 2018), which found significant negative relationships between the anxiety and speaking performance. Conversely, the other two components of vocabulary and grammar as components more related with writing should take a different route and not be so affected by anxiety.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…The structural equation modeling run to answer the first question of the study indicated that all components of speaking were lower than 0.30, showing significance and they all, were in a negative and significant correlation with anxiety, the sample size was adequate for running the model and the structural regression model enjoyed a good fit to show that the components of speaking had significant contributions to their latent variable and all components of speaking performance were in a negative correlation with anxiety. These results are consistent with those of other researchers (Mazouzi, 2013;Thornbury, 2005;Woodrow, 2006;Brown, 2000;Mahripah, 2014;Tanveer, 2007;Kayaoğlu & Sağlamel, 2013;Hanifa, 2018;Baran-Łucarz, 2013;Mahmoodzadeh, 2012;Suleimenova, 2013;Dewaele & Ip, 2013;Leong & Ahmadi, 2017;Subekti, 2018;Zheng & Cheng, 2018;Liu, 2018), which found significant negative relationships between the anxiety and speaking performance. Conversely, the other two components of vocabulary and grammar as components more related with writing should take a different route and not be so affected by anxiety.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…This study found a moderate level of anxiety for international students who were learning Chinese as a foreign language. This finding is consistent with previous research that reported moderate anxiety in the learning of English, Spanish, French, and Chinese (Horwitz, 1986;Liu & Jackson, 2008;Luo, 2018;Rastegar & Karami, 2015;Sellers, 2000;Subekti, 2018;Yu & Watkins, 2008;Zhao & Whitchurch, 2011). The only exception is the study by Le (2004) which investigated American students of Chinese at seven universities in China.…”
Section: Discussionsupporting
confidence: 93%
“…These behaviors in language learning are considered manifestations of second language anxiety, which is defined as "the feeling of tension and apprehension specifically associated with second-language context" (MacIntyre & Gardner, 1994, p. 284). To date, research on second language anxiety has reported about one third to two thirds of learners in second or foreign language classrooms experienced anxiety (Kim, 2000;Shao, Yu, & Ji, 2013;Trang, et al, 2013) ranging from moderate to high based on various anxiety scales (Le, 2004;Luo, 2018;Rastegar & Karami, 2015;Subekti, 2018;Yu & Watkins, 2008;Zhao & Whitchurch, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To Improve the English Language Ability in the context of English Specific Purpose, the teachers or lecturers need to choose the appropriate syllabus and strategies (Dewi, 2015;Hayati, 2015), both teachers and students should minimise the debilitating effects of students' Foreign Language Anxiety (Subekti, 2018), and it is important of building of collaboration between teacher and students. It is suggested that they should work closely to improve the quality of ESP program (Khoirunnisa, Suparno, Supriyadi, 2018)…”
Section: Discussionmentioning
confidence: 99%